3D elemental sensitive imaging by full-field XFCT. Issue 10 (21st May 2015) - Deng, Biao; Du, Guohao; Zhou, Guangzhao; Wang, Yudan; Ren, Yuqi; Chen, Rongchang; Sun, Pengfei; Xie, Honglan; Xiao, Tiqiao
<x xml:space="preserve">Abstract</x> We propose a feasibility study to perform 3D elemental imaging for multiple elements of interest within a single sample using full-field X-ray fluorescence computed tomography (FF-XFCT).